Experimental study on optimization of CO2 huff-n-puff demixing agent for tight conglomerate reservoirs - WU Hairong; WANG Likun; YANG Yulong; SONG Ping; ZHANG Jigang; TAN Long; HOU Jirui (Youqi dizhi yu caishoulu)
The minimum miscible pressure （MMP） of CO2 and crude oil is an important parameter for distinguishing miscible flooding from immiscible flooding of CO2. In addition， effectively reduce the MMP of CO2 and crude oil has become a key issue for enhanced oil recovery in low-permeability reservoirs. To solve the problem that miscible flooding cannot be realized in a block of tight conglomerate reservoir in M Oilfield， Xinjiang， this paper screened the most effective demixing agent through the experimental method of core flooding and evaluated the influence of demixing agent injection on CO2 huff-n-puff effect in cores of tight conglomerate reservoirs. The results show that the MMP of CO2 and crude oil decreases the most when isobutyl citrate is injected， so it is selected as the best demixing agent. At the same temperature， the viscosity of the crude oil decreases as the concentration of isobutyl citrate increases； its viscosity reduction effect on oil is equivalent when the concentrations of isobutyl citrate are 0.6% and 0.8%， respectively. Based on the demixing ability and economy， the injection volume and concentration of isobutyl citrate are determined as 0.006 PV and 0.6%， respectively. The mechanism that isobutyl citrate could decrease the MMP of CO2 and crude oil is the ability to reduce the viscosity of crude oil and promote the extraction capability of CO2. The parameter optimization results of laboratory CO2 huff-n-puff experiments are as follows： The optimal gas injection timing arrives when the pressure failure is 10%； the optimal gas injection volume is 0.75 PV， and the optimal shut-in duration is 15 h. The CO2 huff-n-puff recovery increases from 12.89% without demixing agent injection to 19.36%. The optimized isobutyl citrate has an obvious effect on enhancing CO2 huff-n-puff recovery.